COMPARATIVE VALIDITY OF LEA CONTRAST SENSITIVITY CHART TO PELLI-ROBSON CONTRAST SENSITIVITY CHART IN NEURO-OPHTHALMOLOGY PATIENTS - Valencia, Lovenia; Prihatningtias, Riski (Majalah Oftalmologi Indonesia, 2023)
INTRODUCTION AND OBJECTIVEThe Pelli-Robson and LEA contrast sensitivity chart are widely used to measure clinical contrastsensitivity. The Pelli-Robson is a gold standard with the limitation of its bulky size. The LEAcontrast sensitivity chart offers a reliable test in a way more practical and portable chart. Thiscondition led to a question of whether we can predict Pelli-Robson score based on the LEA score.This study developed a conversion method to facilitate the transition from the LEA to the PelliRobson and validating the conversion score. METHODSThis study retrospectively examined the relationship between LEA and Pelli-Robson ContrastSensitivity Test. There were 120 eyes included in this study. We produced a conversion tableusing the equipercentile equating method. Then, we evaluated the reliability and accuracy of thisalgorithm to convert the LEA to the Pelli-Robson contrast sensitivity score. RESULTSLEA scores were converted to Pelli-Robson scores according to a conversion table that achieveda reliability of 0.91 based on intraclass correlation. The accuracy of this algorithm was 81.6%within 1 point difference from the raw score. CONCLUSIONSThis study reported a reliable and comparable conversion algorithm for transforming LEA scoresinto converted estimated Pelli-Robson scores. This method will enhance the utility of existing datain clinical and research settings.